Yb-Doped Aluminophosphosilicate Triple-Clad Laser Fiber With High Efficiency and Excellent Laser Stability - Shuang Liu; Huan Zhan; Kun Peng; Shihao Sun; Yuwei Li; Li Ni; Xiaolong Wang; Jiali Jiang; Juan Yu; Rihong Zhu; Jianjun Wang; Feng Jing; et al. (IEEE Photonics Journal)
We fully demonstrated an ytterbium (Yb) doped triple-clad laser fiber with intense pump absorption, high efficiency, and laser stability. P5+/Al3+ molar ratio in the central region of fiber core was specially designed to be ∼1.08 for compensating P2O5 evaporation, while the ratio in the outer region was set as ∼0.92 for obtaining a flattened refractive index profile. Applying a two-stage deposition process, one-time collapse technique, low-temperature multi-times sintering, and suitable flow of pure POCl3 during sintering and collapsing process were instrumental in decreasing and offsetting element evaporation. Measured in an all-fiber master oscillator power amplifier configuration, the 7-m-long fiber obtained 1.39 kW near-single-mode laser output at 1079.6 nm with a slope efficiency of 85.2% and a beam quality M2 of 1.36. Output laser spectrum with no sign of nonlinear-related peaks and a narrow 3-dB-bandwidth of ∼0.33 nm was obtained. The fiber-based laser setup was kept at the maximum power for 1 h with power degradation less than 0.21%. The results demonstrated Yb-doped aluminophosphosilicate triple-clad fiber is a highly competitive candidate for commercial high-power laser and high-power narrow-linewidth fiber laser.